Developing a Battery Management System Appropriate for the Electricity Network Scale - FEYZİOĞLU, AHMET (My University, 2022)
Global warming, environmental pollution, CO-NOX problems from fossil fuels and energy scarcity have led governments and industry to seek an alternative solution. Restrictions and bans on the use of fossil fuels have been introduced by many governments to prevent this pollution. This policy aims to provide consumers with an alternative means of transportation and to direct their attention to clean and environmentally friendly resources. Therefore, it shows that renewable energy sources have become a great opportunity to removing carbon and reduce dependence on fossil fuels. The prevalence and share of renewable energy sources in the electrical power system has been increasing. Therefore, concerns have arisen about the reliable and satisfactory operation of the electric power system. With penetration of renewable energy, new challenges have emerged in the energy sector such as suppressing power surges and spinning reserve support capacity. Battery energy storage systems play an important role in renewable energy integration and storage. In this context, while performing all the functions of battery management systems in the retail energy sector; It is aimed to locally produce and develop a new generation, modular and smart battery management system that will offer unique additional innovative solutions to these hardware. The basic functions that should be in the conventional battery management system are; data acquisition, safety protection, battery status determination, charge control, cell balancing and thermal management system. With the technological developments, functions such as data collection, modeling and condition prediction, fault diagnosis, health management, cell balancing, communication, IOT and cloud technologies have been defined. In parallel with technological development, it is seen that the necessary functions have been integrated into the BMS over time. It is aimed to add the developed SoH algorithm and active balance features to the BMS. It has been foreseen that the BMS, which result of the study, will be an innovative, advanced system for energy storage systems suitable for the scale of the electricity grid, and will come to the fore with its originality among its counterparts.
Keywords: BMS (Battery Management System); Electricity generation and management; Energy systems; Solar energy